2009
DOI: 10.1002/jcu.20551
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurement of cross‐sectional area of the median nerve in the diagnosis of carpal tunnel syndrome: Correlation with nerve conduction studies

Abstract: Sonographic measurement of median nerve CSA at the tunnel inlet is a good alternative to NC studies as the initial diagnostic test for CTS, but it cannot grade the severity of CTS as well as NC studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
87
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 21 publications
10
87
2
3
Order By: Relevance
“…However, sonography did not determine the severity of CTS. In Moran's study, a cross-sectional area greater than 13 mm was diagnostic for CTS [18]. The current study confirmed those results.…”
Section: Discussion ____________________________supporting
confidence: 87%
“…However, sonography did not determine the severity of CTS. In Moran's study, a cross-sectional area greater than 13 mm was diagnostic for CTS [18]. The current study confirmed those results.…”
Section: Discussion ____________________________supporting
confidence: 87%
“…Although ultrasound is unable to evaluate proximal etiologies of carpal tunnel-like symptoms, it does have the ability to detect other causes of compression in the carpal tunnel such as space-occupying lesions and tenosynovitis [18,19,26]. Although some studies have confirmed the utility of ultrasound in the diagnosis of CTS, their small sample size and the heterogeneity of study design has made it difficult to draw definitive conclusions regarding the sensitivity and specificity of ultrasonographic measurement of the median nerve in the diagnosis of CTS [17,22,24]. In this meta-analysis, we determined the sensitivity and specificity of ultrasound as a diagnostic tool for CTS.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be due to difference in the sample size, study design and patient's characteristics. In most previous studies, concordance of NCS and ultrasound findings in defining the severity of CTS has been reported (De Krom et al, 2009;Mohammadi et al, 2010;Moran et al, 2009;Pazzaglia and Padua, 2010).…”
Section: Discussionmentioning
confidence: 55%